Energia eólica aplicada ao bombeamento da água para irrigação por gravidade na agricultura familiar - Feitosa, Erialdo de Oliveira (2014)
The use of wind energy is today a reality in the Brazilian energetic context, because it meets the requirement of complementarity to the national energy system and its exploitation generates relatively few environmental impacts. In this context family agriculture, which lives together with semiarid, passes per great bottlenecks with relation to the access, and the cost of two resources fundamental for its development, water and energy. This project was developed with bias in the supply of water and energy to small rural properties focused on horticultural. So that wind energy can be an important solution for the process of production of agriculture, because it can supply the needs of the small producer. Thus the objective of this research was to investigate the possibility of a wind turbine to generate electricity to put in action an water pumping system which represses water to an elevated reservoir, and possibly could be used for irrigation per gravity drip. It was used a 1 kW wind generator power, model H3.1-1KW, Hummer mark, where it and the pumping system were installed at the Federal University of Ceará, Campus do Pici. With the experimental arrangement ready, it was conducted to collect data on wind speed, current and voltage generated by, and pressure and flow rate of the motor pump. As a result it was verified a pumped volume averaged 3750.5 L day-1. Concluding that can be used in irrigated horticultural production family agriculture and would also be useful in animal production and consumption own. This conclusion presents wind power as a good alternative for family agriculture live with the semiarid in the sense which will enable the use of renewable energy linked the rational use of water.